Opinião e receptividade: a percepção dos alunos de Escolas de Ensino Médio da rede estadual de ensino do município de Santarém- Pará sobre a utilização da plata- forma digital QUIZIZZ em aulas de biologia - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Nowadays, it is very common to notice that the student's attention is more focus on digital device than on their teacher. Keeping this in mind, the teacher is responsible to find ways to catch student's attention in class, and the usage of technological resources is one of the manners to help teaching and learning process. Therefore, Information and Communication Technologies (ICTs) contributes to the classes in order to make the school environment more pleasant and technological for students, as the case of digital platforms used in learning process. The aim of this research was to find out the opinion of students and how they accept the use of technologies in biology teaching. To evaluate the development and appraisement of technologies in biology teaching in the classroom to assimilate, understand and make content evaluation, it was necessary to visit some high schools under State Government support that are located in the municipality of Santarém, in the western region of Pará State. Quizizz was an educational platform used during the biology classes. Questionnaires and observation were applied with students to reach the answers for this project. The total number of schools that participated in the survey were 4, with 183 participants from 9 different classes. It was possible to highlight some positive points, such as the students' motivation and interest in participating in different classes, and their acceptance of teaching methods that run off from the traditional methods. And as a negative point was the lack of internet to access the platform during the use of this methodology causing the student discouraged by using digital platforms, once they were not be able to participate in classes when technologies were used. In this context, it is necessary to have an attentive approach by the teacher when inserting these technologies during biology classes, to integrate all students in the class during the activity proposed.
Keywords: Jogo; Aprendizagem; Avaliação; Plataformas digitais; CNPQ:: CIÊNCIAS BIOLÓGICAS